'Steely Velvet': The Voice of James Mason. Issue 1 (January 2015) - Garvey, Adrian
<x xml:space="preserve">Abstract</x> This article argues that, although the subject of film sound is a developing field of interest in film studies, the voice, despite its centrality to issues of performance and stardom, remains an under-examined subject within the discipline. It considers some existing work on the topic and proposed methodologies for the analysis of voice and performance. The work of James Mason is used as a case study, offering an overview of his career and a discussion of the changes in his star persona and performance style as he moved from star to character actor. Consideration is given to the ways in which Mason's distinctive voice became the defining aspect of his star persona and a subject for impersonation. Critical responses to his vocal style throughout his career are examined and sequences from three Mason films, The Pumpkin Eater (1964), Fanny by Gaslight (1944) and The Upturned Glass (1947) are analysed in order to explore Mason's use of voice and gesture in detail.